Bovine derived hydroxyapatite-samarium oxide composites for biomedical applications - (:unkn) unknown (Metal Powder Industries Federation, 2017)
This study is related to whether bovine derived hydroxyapatite (BHA)-samarium oxide (Sm2O3) composites can be used for biomedical applications or not. The rates of Sm2O3 were used wt% 1, 3 and 5. The pellets were prepared in uniaxially mold at 350 MPa and then fired at various temperatures ranging from 900oC to 1300oC with the dwell time of 3 h. To analyze microstructural changes during sintering, SEM and XRD analysis were used. Mechanical properties of sintered samples were evaluated by a series test such as density, hardness and compressive strength. Experimental results showed that grain growth of BHA can be avoided by the addition of Sm2O3 addition. Monolithic BHA is stable up to 1300oC, while the BHA- Sm2O3 composites stable up to 1200oC. BHA-%3Sm2O3 can be used in biomedical applications because it has enough compressive strength of 152 MPa. © 2017 Metal Powder Industries Federation. All Rights Reserved.